Pengaruh Metode Student Facilitator and Explaining (SFE) terhadap Kemampuan Menceritakan Kembali Isi Cerpen pada Siswa SMPN 1 Cigeulis, Pandeglang - Saraswati, Saraswati (Jurnal Artikula, 2018)
The aim of this study is to determine the level of students’ ability to retell the contents of short stories by using Student Facilitator and Explaining (SFE) methods and the level of students’ ability in knowing the ability to retell the contents of short stories with the expository method and knowing the effect of SFE methods on the ability to retell the contents of short stories in class VIII students of SMPN 1 Cigeulis, Pandeglang District, Academic Year 2018/2019. This study used an experimental method and was conducted at SMPN 1 Cigeulis Pandeglang District Academic Year 2018/2019 by taking the eighth-grade students in academic year 2018/2019. The sample technique uses purposive sampling, namely class VIII A as an experimental class and class VIII B as a control class. Based on the results of data processing, it was obtained an illustration that the ability to retell the contents of short stories using the Student facilitator end explaining method in class VIII of SMPN 1 Cigeulis Pandeglang District in academic year 2018/2019 was very good. These results show that the average ability is 63.6 while students who get above the average score is 72.2% and those who score below the average of 34.4% of the highest score of 80, and the lowest score of 45. While the ability to retell the contents of short stories using the expository method is still lacking, it is shown that the average learning outcomes are 53.1 while students get above the average is 73.3% and those who get a score below average 30% from the highest score of 70 and the lowest value of 35. From the calculation of statistics obtained the results of hypothesis testing (t-test) with a significant level of 5% that is t count greater t table 7.332. It shows that there are differences in the ability to retell the contents of short stories that use the SFE methods to obtain higher learning outcomes when compared to using the expository method.